A study of how Israel gives back to the U.S. in terms of military technology for the foreign military funds received - Law, Daniel Zhen Yi (2015)
In the first section of the main paper, this paper will first ascertain the amount of aid given to Israel in the past three decades and determine how much of the aid was meant for military development purposes. Subsequently, this paper will then investigate the growth of the Israeli military and the technological advancement in its military hardware, attributable to the aid given by the US. This will demonstrate the degree of aid given to Israel by the US, not in terms of dollars and cents, but in terms of the effects it has on the Research and Development (R&D) progress of Israel. To disprove that Israel has nothing to offer for the US, and that the US was at a losing end of the bargain, this paper will also consider three case studies on instances where the Israel Defense Force (IDF) aided the US armed forces in various operations. The three cases are namely: Israel's contribution to the first Gulf War in 1991; Israel's support in Kosovo Operations in 1999; and Israel's aid in the US campaign in Iraq in 2003. In each case study, this paper will consider the effects of Israeli aid to the US operations and attempt to put a value to the "aid" given by the IDF. Finally, this paper will conclude by providing several policy recommendations for the future of the US-Israeli relations with respect to military relations.